Impact of students’ learning preferences in an entrepreneurial university - Naila Aaijaz; Noraani Mustapha; Yah Awg Nik; Wan Mohd Yusuff Wan Ibrahim (International Business Information Management Association, 2013)
This paper aims to study the use of latest web-based tools like Web2.0 technology to do online learning. The Web 2.0 based learning may involve the use of blogs, Wikis, online social community (e.g. Facebook, Twitter), Dropbox – a file hosting service that offers cloud storage, file synchronization and client software, online video sharing (e.g. YouTube), online video and audio conferencing tool, and social virtual environment (e.g. Second life). Web 2.0 has provides rich web tools to help student’s have better learning platform and ensures far-reaching impact on the student’s performance. Furthermore, this technology can support education in terms of participation, interaction, sharing of knowledge, social networking, critical reading, critical thinking and writing, collaboration, and expression of opinions. Design/methodology/approach–An empirical study (quantitative) has been conducted on the selected respondents randomly. A random sample of 100 respondents is adopted by the questionnaire survey method. The results will be obtained on measuring the students’ performance after the students’ adopt Web 2.0 Technology for learning purpose. Findings – The finding in this study present the perception and awareness of students on Web 2.0 technology and its influence on their academic performance. Based on regression analysis, the results indicated that the two factors awareness and perception of students’ on the use of web 2.0 technology significantly relates to students’ academic performance. Overall outcome of this study is that the use of Web 2.0 technology in higher education is quite positive. From the students’ perspectives when analyzed it suggests that they clearly realize the benefits of the use of Web 2.0 tools in their education. Originality/value – While the importance of this study are to provide evidence that most students feel that integrating Web 2.0 in context of learning can be effective at improve their learning ability. From a research perspective, the results demonstrate the use of Web 2.0 tools has significant potential to support and enhance in-class teaching and learning in higher education.